A burden of knowledge: A qualitative study of experiences of neonatal intensive care nurses' concerns when keeping information from parents. (December 2015) - Green, Janet; Darbyshire, Philip; Adams, Anne; Jackson, Debra
Improved life-sustaining technology in the neonatal intensive care has resulted in an increased probability of survival for extremely premature babies. In the neonatal intensive care, the condition of a baby can deteriorate rapidly. Nurses and parents are together for long periods at the bedside and so form close and trusting relationships. Neonatal nurses as the constant caregivers may be presented with contradictory demands in attempting to meet the baby's needs and being a patient and family advocate. This article aims to explore the issues arising for neonatal nurses when holding information about changes to a condition of a baby that they are unable to share with parents. Data were collected via interviews with 24 neonatal nurses in New South Wales, Australia. A qualitative approach was used to analyse the data. The theme 'keeping secrets' was identified and comprised of three sub-themes 'coping with potentially catastrophic news', 'fear of inadvertent disclosure' and 'a burden that could damage trust'. Keeping secrets and withholding information creates internal conflict in the nurses as they balance the principle of confidentiality with the parent's right to know information. The neonatal nurses experienced guilt and shame when they were felt forced by circumstances to keep secrets or withhold information from the parents of extremely premature babies.